2011
DOI: 10.1158/1055-9965.epi-11-0267
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Suboptimal Human Papillomavirus Vaccine Uptake Among Ethnic Minority Girls

Abstract: Background The introduction of HPV vaccines represents a breakthrough in the primary prevention of cervical cancer. However, little is known about vaccination uptake and correlates among U.S. low-income, ethnic minority and immigrant populations who may benefit most from the vaccine. Methods Telephone interviews (N=490) were conducted in six languages between January and November 2009 among mothers of vaccine-eligible girls (ages 9–18) using the Los Angeles County Department of Public Health, Office of Women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
119
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(135 citation statements)
references
References 23 publications
15
119
1
Order By: Relevance
“…Several studies have shown that parental knowledge and awareness of HPV vaccine is a strong predictor of vaccine receipt or intention to vaccinate. 13,14 High attitude and belief scores were associated with HPV series completion as well. A cohort study by Fishman et al that only measured HPV knowledge among parents and adolescents found knowledge was not a significant predictor of vaccination behavior and suggested that beliefs and attitudes are more predictive of vaccination behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that parental knowledge and awareness of HPV vaccine is a strong predictor of vaccine receipt or intention to vaccinate. 13,14 High attitude and belief scores were associated with HPV series completion as well. A cohort study by Fishman et al that only measured HPV knowledge among parents and adolescents found knowledge was not a significant predictor of vaccination behavior and suggested that beliefs and attitudes are more predictive of vaccination behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…This study is unique in that it focuses on a racially and economically diverse sample of adolescents coming from a mix of urban and rural schools, whereas previous HPV studies with parents were conducted prior to ACIP recommendations for HPV vaccination of males, focused on female adolescents only, or relied primarily on health care facilities for recruitment. [12][13][14][15] by Medicaid (59.8%, n D 410) and were enrolled in middle school (63.6%, n D 436) ( Table 1). Only 48.5% (n D 333) of adolescents had received one dose of the HPV vaccine ( Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Although barriers to vaccine uptake are well documented in the literature, particularly among African American females, our study population reported willingness to receive the vaccine when people perceived the vaccine as available at no cost. Reported facilitators of HPV vaccine uptake are knowledge of HPV vaccine [43], higher perceived severity of HPV infection [43][44][45], and having private health insurance [46,47]. Facilitators for both uptake and series completion include unmarried status [35], vaccine history [35,44,46], and subjective norms endorsing HPV vaccination uptake [42,44,[47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…This reflects minimal improvement over the past few years and reaching a plateau for female vaccination at a level dramatically lower than Healthy People 2020's goal of an 80 % completion rate. Site-based studies in the US have reported even lower rates of HPV vaccine completion, ranging between 1.9 and 26.5 % among female adolescents [9][10][11] and between 1.3 and 4 % among male adolescents [12,13].…”
mentioning
confidence: 99%